ANALISIS POTENSI BENCANA ALAM BANJIR ROB DI KOTA BENTENG KABUPATEN KEPULAUAN SELAYAR - Fadillah, Nur; Rusdi, Rusdi; Padli, Feri (xxxx-xxxx, 2023)
The aim of the research is to find out 1) Potential for Natural Disasters Flood Rob in the Fort City of the Selayar Islands Regency. 2) Disaster Mitigation Efforts Rob Flood Nature in Benteng City, Selayar Islands Regency. Types of research used is descriptive. Data collection techniques used in this study were observation, interviews, and documentation, Data analysis was carried out using 3 (three) stages, namely stages data reduction, data presentation and conclusion. The results of the study show that: 1) The potential for tidal floods in the Citadel City most significantly influenced by the height of the land, the distance from coast and land use. The relatively low elevation of the Citadel City grounds cause when there is a tide, the water will quickly inundate residential area. In addition, the distance of Fort City's mainland from the coast so close that it affects the elevation of the ground surface. The mainland having a close distance to the beach tends to have a lower elevation makes it vulnerable to tidal flooding. One of the natural factors is the occurrence of flooding rob in Benteng City is the ebb and flow of sea water accompanied by heavy rainfall altitude, topographical conditions, and climate change. Then the human factor including, careless waste disposal and drainage channels that are not properly managed, then the most severe is the damage to the embankment coast guard. 2) Efforts to deal with the tidal flood natural disaster in Benteng City Some of them are carried out through: Human approach, namely conducting counseling about impending disaster threats and preparedness training community to deal with tidal floods. Then go through the approach administrative, namely conducting outreach about flood management and risk, conduct education and simulation on how to do it to prevent the risk of tidal flooding, and to cooperate or coordinate with central government, regions and local communities. Next is cultural approach, the efforts made by the community in dealing with the threat of tidal flooding is by cultivating to maintain sustainability with nature with the belief that by taking care of nature, nature too will protect them from the disaster that will happen.